Microbiological, steady, and dynamic rheological characterization of boza samples: temperature sweep tests and applicability of the Cox-Merz rule - Arici, Muhammet; Ersoz Tatlisu, Nevruz Berna; Toker, Omer Said; Yilmaz, Mustafa Tahsin; Cankurt, Hasan; Durak, M. Zeki; Sagdic, Osman (Tubitak Scientific & Technological Research Council Turkey, 2014)
Boza is a beverage produced by lactic acid bacteria (LAB) and yeast, which affects rheological properties. In the present study, boza samples collected from a local market were characterized with reference to microbiological and rheological approaches. The boza samples were characterized with respect to their microbiological population, i.e. the numbers of LAB and yeast. The numbers of LAB and yeast were found to range from 2.88 x 10(6)to 2.06 x 10(10) CFU/mL and from 3.71 x 10(3)to 9.40 x 10(5) CFU/mL, respectively. Their steady and dynamic rheological properties were investigated within the temperature range of 0-50 degrees C. Apparent viscosity values (n) of the boza samples decreased with shear rate, indicating that the samples behaved as a pseudoplastic fluid. The Ostwald-de Waele model satisfactorily described (R-2 > 0.99) the flow behavior of the samples at 5 and 20 degrees C. Storage modulus (G') values were higher than loss modulus (G ''), indicating that boza samples had a solid-like structure. Temperature had a remarkable effect on the steady and dynamic properties of the samples; therefore, temperature sweep tests were also conducted to determine temperature dependency of the samples. The n(50), G', and G '' values decreased with increase in temperature. The Arrhenius equation could be satisfactorily used to describe changes in these parameters depending on temperature. A modified Cox-Merz rule with shift factors ranging from 1.0 to 2.2 was successfully applied to put forward a relationship between steady shear and dynamic shear viscosity data.
Keywords: Arrhenius; boza; Cox-Merz rule; dynamic and steady shear; temperature sweep; LACTIC-ACID BACTERIA; HOT CHOCOLATE BEVERAGE; FERMENTED BEVERAGE; CEREAL BEVERAGE; BEHAVIOR; MIXTURES; XANTHAN; FOODS; IDENTIFICATION; OPTIMIZATION; Agriculture; Forestry